Application of Numeracy Learning Movements Using Pianika Musical Instruments in the 7th Batch of the Program Kampus Mengajar at UPTD SD Inpres Beiposo, Nusa Tenggara Timur, Indonesia - Selis, Elias Fernando; Dopo, Ferdinandus Bate; Fikri, Kanzul; Samino, Sena Radya Iswara (SAINTIS Publishing, 2024)
This study aims to enhance students' interest and motivation in numeracy learning through an interactive and engaging approach using pianica musical instruments as learning media. By integrating music into numeracy learning, the study seeks to create a fun and effective educational experience. The research employed a three-stage process: planning, implementation, and evaluation. Data were collected by administering numeracy tests to students before and after the implementation of the pianica-based learning approach. The data analysis involved comparing the results of these tests to measure the effectiveness of the intervention. The findings demonstrate that the application of numeracy learning using pianica musical instruments at UPTD SD INPRES Beiposo significantly improved students' numeracy skills. The average scores from the numeracy tests showed a marked increase after the implementation. This approach not only facilitated a better understanding of mathematical concepts but also heightened students' learning motivation by fostering a more interactive and enjoyable learning environment. The implementation of numeracy learning using pianica musical instruments under the Kampus Mengajar Program has delivered substantial benefits, improving the quality of education for both students and participating university students. For students, this method effectively enhanced their numeracy skills and learning engagement. Meanwhile, for university students, the program provided valuable opportunities to develop their potential and expand their knowledge beyond campus life. Moving forward, it is recommended to continue and refine this program by enhancing supporting facilities, such as musical instruments, and involving more stakeholders, including parents and local communities, to foster greater student participation and outcomes. Additionally, exploring the use of other musical instruments in numeracy learning could further expand its effectiveness and interactivity.